Sincronização da ovulação para inseminação artificial em tempo fixo (IATF) em fêmeas bubalinas (Bubalus bubalis) na Amazônia equatorial - Bezerra, Danilo Cutrim (2016)
The aim of the study was to evaluate different synchronization protocols for timed artificial insemination (TAI) in buffalo during the breeding and nonbreeding seasons, in the equatorial Amazon. The experiment was conducted in Baixada Maranhense, Maranhão, Brazil. A total of 200 lactating Murrah buffalo (Bubalus bubalis) cows, raised extensively on native pasture, water and minerals ad libitum were used. Based on retrospective historical distribution of births in the region, the reproductive seasonality was characterized in two seasons, Breeding (July) and Nonbreeding (January). Then four protocols for ovulation synchronization were performed: "GnRH/hCG" (control protocol for Breeding season); "GnRH/BE" (proposed protocol for Breeding season; "P4/hCG" (control protocol for Nonbreeding season); "P4/BE" (proposed protocol for Nonbreeding season). The females were ultrasonographically examinated for monitoring the follicular dynamics and ovulation. Then were timed artificially inseminated to evaluate the conception rates. All treatments were effective to induce follicular growth from emergence until follicular deviation. There was effect of the ovulation inducer on diameter of dominant and ovulatory follicles (P<0.05). The ovulation rate was higher in hCG-treated (65%) animals than in BE-treated (30%), regardless of breeding season. The ovulation rates were similar between seasons, regardless of synchronization protocol. In general, ovulations occurred in 55% of synchronized females in Breeding season and only in 40% during Nonbreeding (P = 0.31), despite the use of progesterone devices. The hCG-induced ovulations were 21.4 hours earlier than in BE-induced in Breeding season and 24.0 hours earlier in the Nonbreeding season. The average conception rate was 29% (29/100) in Breeding season and only 3% (3/100) in Nonbreeding season (P<0.01), but no difference between protocols in the same season. We conclude that the hCG was more efficient to induce ovulation than estradiol benzoate and it was not possible to obtain satisfactory pregnancy rates in Nonbreeding season in buffalo raised extensively on native, poor and periodically flooded grasslands of the Equatorial Amazon.